The ScholarLed Consortium: OA Monograph Publishing and ‘Scaling Small’ - Barnes, Lucy; Gatti, Rupert (Septentrio Conference Series, 2019)
Watch the VIDEO. ScholarLed, a consortium of five not-for-profit, scholar-led OA book publishers, was founded in 2018 in order to develop powerful, practical ways for small-scale, scholar-led Open Access presses to grow and flourish in a publishing landscape that is changing rapidly. We comprise Mattering Press, meson press, Open Book Publishers, Open Humanities Press, and punctum books: five publishers with different business models and publishing practices, but with a shared commitment to making high-quality research available OA without levying Book Processing Charges (BPCs). We have approached this task with the philosophy of ‘scaling small’; in other words, rather than seeking to grow our reach by any one of us becoming exponentially larger, we want to create systems that allow a large number of diverse, small-scale scholarly publishing initiatives to operate collaboratively, and so to foster a robust, inclusive and community-managed publishing ecosystem in partnership with all actors in the scholarly publishing ecosystem (including scholars, libraries, and funders). Collectively the ScholarLed presses have now published over 500 books, and expect to publish over 80 new titles in the coming year. What would the publishing landscape look like if, rather than 5 presses, we were 25, 50, or 100 in number? Accordingly, in our first year we became key partners in the Community-led Open Publication Infrastructures for Monographs (COPIM) project, which we developed along with organisations including Coventry University; Loughborough University Library; University of California, Santa Barbara (UCSB) Library; Directory of Open Access Books (DOAB); Jisc Collections; and the Digital Preservation Coalition (DPC). In June of this year, this project successfully secured funding of £2.2 million from Research England to build the necessary open infrastructure over the next three years to transform open access book publishing, by moving away from a model of competing commercial service operations to a more horizontal and cooperative, knowledge-sharing approach. In this presentation, we will discuss the ‘scaling small’ philosophy that underlies ScholarLed, and how this chimes with growing international movements such as the Invest in Open Infrastructure initiative. We will also explore how this impacts the COPIM project and our firm conviction that, in order for open access publishing initiatives to thrive, we have to develop more robust definitions of ‘open’ that go beyond releasing content from behind paywalls. COPIM will pilot a range of interventions, from developing open, transparent, sustainable, and community-governed infrastructures for the curation, dissemination, discovery, and long-term preservation of open content and open data, to helping publishers transition away from a BPC-based business model, to following the best practices for integrating open content into institutional library, digital learning, and repository systems. COPIM prepares the ground for OA publishing to thrive, increasing its strength and heterogeneity within a robust, inclusive and community-managed publishing ecosystem: Scaling Small. Keywords: scholar-led; community-driven; open access publishing.